Luminosity Distance and Extinction by Submicrometer-sized Grains - R. Siebenmorgen; Frank Heymann; R. Chini (The Astrophysical Journal Letters)
The distance to the stars is a fundamental parameter, which is determined via two primary methods—parallax and luminosity. While the parallax is a direct trigonometric method, the luminosity distance is usually influenced by interstellar extinction. As long as the optical properties of dust grains are wavelength-dependent this contamination can be corrected. However, as the grain size increases, the extinction properties become gray, meaning these particles contribute by a constant at wavelengths $\lesssim $ 1 μ m, making them undetectable by photometry in the optical. In this study, we compare the parallactic and luminosity distances of a pristine sample of 33 well-known early-type stars with nonpeculiar reddening curves and find that the luminosity distance overestimates the parallactic distance in 80% of the cases. This discrepancy can be removed when incorporating a population of large, submicrometer-sized dust grains in a dust model that provides gray extinction, which diminishes the luminosity distance accordingly.